Before an Analyst Becomes an Analyst: Does Industry Experience Matter? - BRADLEY, DANIEL; GOKKAYA, SINAN; LIU, XI (Journal of Finance, 2017)
ABSTRACT Using hand‐collected biographical information on financial analysts from 1983 to 2011, we find that analysts making forecasts on firms in industries related to their preanalyst experience have better forecast accuracy, evoke stronger market reactions to earning revisions, and are more likely to be named Institutional Investor all‐stars. Plausibly exogenous losses of analysts with related industry experience have real financial market implications—changes in firms’ information asymmetry and price reactions are significantly larger than those of other analysts. Overall, industry expertise acquired from preanalyst work experience is valuable to analysts, consistent with the emphasis placed on their industry knowledge by institutional investors.